2023
DOI: 10.22438/jeb/44/5/mrn-5099
|View full text |Cite
|
Sign up to set email alerts
|

A critical review on occurrence, distribution, environmental impacts and biodegradation of microplastics

G.P. Avinash,
s. Karthick Raja Namasivayam,
R.S. Arvind Bharani

Abstract: Microplastics are small plastic particles (<5mm) linked by hydrocarbon atoms. Microplastics are of two types: primary microplastics, which are inadvertently released into the ecosystem as microbeads, plastic pellets and plastic fibres and secondary microplastics, derived from primary microplastics, when macroplastics get decomposed in the presence of UV light or weathering. Sources of contamination by microplastics can be classified as Terrestrial sources and Aquatic Sources. Microplastics are widespread in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Moreover, the environmental degradation involving radiation, thermolysis and microbial degradation transforms primary MPs to hazardous secondary microplastics in the marine ecosystem (Pourebrahimi and Pirooz, 2023). The negative impacts of microplastics are available at all stages of foodweb, exposure route, and interaction with several pollutants (Avinnash et al, 2023). The tiny size of MPs accumulate easily through the ingestion route of marine organisms like: bivalves, mussels, fishes, shrimps and oysters (Auta et al, 2017;Sulaiman et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the environmental degradation involving radiation, thermolysis and microbial degradation transforms primary MPs to hazardous secondary microplastics in the marine ecosystem (Pourebrahimi and Pirooz, 2023). The negative impacts of microplastics are available at all stages of foodweb, exposure route, and interaction with several pollutants (Avinnash et al, 2023). The tiny size of MPs accumulate easily through the ingestion route of marine organisms like: bivalves, mussels, fishes, shrimps and oysters (Auta et al, 2017;Sulaiman et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…[23] Studies have shown that nanomaterials could be effectively applied for the adsorption of microplastics from marine environment. [24,25] Pourabadeh et al [26] used iron nanoparticles for the removal of reactive red 2 from aqueous solution. Shojaei et al [27] studied NaX nanozeolites for the removal of auramine-O and malachite green dyes from aqueous media.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, chitosan derived nanocomposite was used for the removal of disperse red 60 dye which is found in industrial effluent [23] . Studies have shown that nanomaterials could be effectively applied for the adsorption of microplastics from marine environment [24,25] . Pourabadeh et al [26] .…”
Section: Introductionmentioning
confidence: 99%